Sex and Gender Diversity in Southeast Asia - Douglas Sanders (Journal of Southeast Asian Human Rights, 2020)
The United Nations human rights system has recognized rights of lesbian, gay, bisexual, transgender and intersex individuals (LGBTI), with key decisions in 2011 and 2016. To what extent are the rights of these groupings respected in Southeast Asia? The visibility of LGBTI is low in Southeast Asia and government attitudes vary. Criminal laws, both secular and Sharia, in some jurisdictions, have prohibitions, but active enforcement is rare. Discrimination in employment is prohibited by law in Thailand and in local laws in the Philippines. Change of legal ‘sex’ for transgender individuals is sometimes possible. Legal recognition of same-sex relationships has been proposed in Thailand and the Philippines, but not yet enacted. Marriage has been opened to same-sex couples in neighboring Taiwan. Laws on adoption and surrogacy generally exclude same-sex couples. So-called ‘normalizing surgery’ on intersex babies needs to be deferred to the child’s maturity, to protect their health and rights.